Pre-sleep experiences shape neural activity and dream content in the sleeping brain - Deniz Kumral; Jessica Palmieri; Steffen Gais; Monika Schönauer (iScience)
Summary: Dreams incorporate recent experiences, and memory-related brain activity is reactivated during sleep, suggesting that dreaming, memory consolidation, and reactivation are tightly linked. We devised a paradigm to investigate whether memory reprocessing during sleep contributes to dreaming. Participants listened to different audiobooks before falling asleep, introducing dissimilar experiences to be processed at night. We show that audiobook content was reprocessed at the neural level using multivariate pattern analyses. Brain activity during rapid eye movement sleep, particularly in the beta range, carried information about the audiobook. While the amount of neural reinstatement did not correlate with memory retention, global beta power during REM sleep was associated with better memory performance. Moreover, blind raters could determine which audiobook participants had studied based on dream reports. Participants who dreamt of the audiobook also showed stronger neural reinstatement. Reprocessing of pre-sleep experiences during sleep may thus shape our brain activity, our dreams, and our memories.